Effects of temporal framing and hazard experience on receptivity to hurricane risk messages: A survey of U.S. Gulf Coast residents - Retchless, David P.; Ross, Ashley D. (Frontiers in Communication, 2022)
As knowledge in the scientific community increases regarding how anthropogenic CO2 loading of the atmosphere will impact future hurricane activity, the need for effective and accurate communication of hurricane risk in coastal communities – specifically to non-scientific stakeholders – also increases. To better inform hurricane risk communication, this study employs a survey of U.S. Gulf Coast residents immediately following the active 2017 hurricane season to consider how message framing (as established by communicator word choice) and stakeholders’ experience may affect receptivity to hurricane hazard information. Specifically, it tests how respondents’ perceptions of hurricane risk varied with prior experience and following exposure to randomly assigned, infographic-based depictions of trends in major hurricane (≥ category 3, Saffir Simpson Scale) frequency. The set of randomly assigned infographics varied in both temporal framing (past-to-present trends based on paleo data versus present-to-future trends based on climate projections) and causal framing (‘climate change’ versus ‘ocean and atmospheric change’). The results suggest that recent, damaging hurricane experience may be associated with a tendency towards increasing hurricane risk perceptions after viewing the infographics. For framing effects, temporal framing of hurricane risk messages matters, with forward-looking framings (future projections) causing increased perceptions of risk and storm frequency; effects of causal framing were not significant. The results also show that Gulf Coast residents tend to be more optimistic about the future frequency of major hurricanes than most scientists and, consistent with confirmation and optimism biases, are somewhat resistant to changing their prior risk beliefs based on infographic exposure. Communicators should consider these factors when translating scientific hurricane risk information to the public.